2010
DOI: 10.1029/2010gl045258
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between aerosol oxidation level and hygroscopic properties of laboratory generated secondary organic aerosol (SOA) particles

Abstract: Laboratory experiments investigated the relationship between oxidation level and hygroscopic properties of secondary organic aerosol (SOA) particles generated via OH radical oxidation in an aerosol flow reactor. The hygroscopic growth factor at 90% RH (HGF90%), the CCN activity (κORG,CCN) and the level of oxidation (atomic O:C ratio) of the SOA particles were measured. Both HGF90% and κORG,CCN increased with O:C; the HGF90% varied linearly with O:C, while κORG,CCN mostly followed a nonlinear trend. An average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
383
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(422 citation statements)
references
References 74 publications
36
383
3
Order By: Relevance
“…To encompass the difficulty of representing the full molecular composition, the O : C of SOA has been included in global climate models to provide a description of the aerosol aging (Tost and Pringle, 2012). Furthermore, a number of recent studies have reported a positive correlation between hygroscopicity and bulk O : C for both laboratory and ambient SOA (Massoli et al, 2010;Jimenez et al, 2009;Chang et al, 2010;Duplissy et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…To encompass the difficulty of representing the full molecular composition, the O : C of SOA has been included in global climate models to provide a description of the aerosol aging (Tost and Pringle, 2012). Furthermore, a number of recent studies have reported a positive correlation between hygroscopicity and bulk O : C for both laboratory and ambient SOA (Massoli et al, 2010;Jimenez et al, 2009;Chang et al, 2010;Duplissy et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…however, that κ org has been observed to be higher in other studies, especially when the organic aerosol becomes more oxygenated that is when chemical aging has taken place(e.g., Chang et al, 2010;Massoli et al, 2010). At an O:C ratio of 0.2, i.e.…”
Section: Hygroscopicity Parameter Kappa (κ) and Ccn Closurementioning
confidence: 99%
“…CC BY 4.0 License. Duplissy et al, 2008;Frosch et al, 2011;Jimenez et al, 2009;Massoli et al, 2010;Wong et al, 2011). In addition, several studies have investigated the effect of organic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the gas-particle partitioning of atmospheric aerosol is necessary for effective OA modeling and prediction of the aerosol budget ). Furthermore, understanding the contribution of SOA to aerosol number and hygroscopicity is important for prediction of cloud condensation nuclei (CCN) (Kanakidou et al 2005;Roelofs 2008;Asa-Awuku et al 2009;Chang et al 2010;Massoli et al 2010;Engelhart et al 2011;Lambe et al 2011;Riipinen et al 2011;Gantt et al 2012).…”
Section: Introductionmentioning
confidence: 99%